2022
DOI: 10.1590/0034-7167-2021-0128
|View full text |Cite
|
Sign up to set email alerts
|

Profile of nursing diagnoses in indigenous older adults in the community: a cross-sectional study

Abstract: Objective: to describe the profile of nursing diagnoses evidenced in indigenous elderly in the community. Methods: this is a cross-sectional study, carried out with 51 indigenous elderly people of Potiguara ethnicity, through a nursing consultation. The clinical data, obtained from the consultation, were analyzed following Risner’s diagnostic reasoning process and the NANDA-I Taxonomy (2018-2020). For greater accuracy, the diagnoses obtained underwent peer review by a specialist. Results: 37 diagnoses were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Our study reports urinary incontinence prevalence from 3-81%. Only one publication in our study reported the prevalence of fecal incontinence experienced by older Indigenous adults at 2% [52]. A recent systematic review and meta-analysis identified a global prevalence rate of 8.0% [54].…”
Section: Patternsmentioning
confidence: 87%
See 1 more Smart Citation
“…Our study reports urinary incontinence prevalence from 3-81%. Only one publication in our study reported the prevalence of fecal incontinence experienced by older Indigenous adults at 2% [52]. A recent systematic review and meta-analysis identified a global prevalence rate of 8.0% [54].…”
Section: Patternsmentioning
confidence: 87%
“…This variability can be explained by several factors including severity of symptoms (e.g., mild vs severe erectile dysfunction, grading of pelvic organ prolapse), life course (e.g., pregnancy vs post-partum, peri-vs post-menopausal), structure causing the symptoms (e.g., uterocele, cystocele, rectocele), and symptom presentation (e.g., urge incontinence, stress incontinence, mixed incontinence). There was one report of accidental bowel leakage (fecal incontinence) experienced by 2% of older Indigenous adults [52].…”
Section: Fig 4 -Frequency Of Pelvic Health Conditions Described In Th...mentioning
confidence: 99%
“…O fenômeno do envelhecimento humano também ocorre entre as populações indígenas, que, por sua vez, é um assunto pouco explorado pela literatura, sobretudo, no âmbito da saúde (Silva et al, 2022;Borghi;Carreira, 2015). Segundo o novo censo do Instituto Brasileiro de Geografia e Estatística (IBGE) de 2022, a população indígena do Brasil é composta por 1.693.535 pessoas (Brasil, 2022).…”
Section: Introductionunclassified